Network approach based on community forestry management: stakeholders management methodology for forestry governance of peruvian amazon - Tostes, Marta; Motta, Claudia (Revista de Administração da UFSM, 2018)
The study aims to develop the governance issue in the Amazon as a means to access international markets. The articulation of organizations involved in Community Forest Management promotion was measured on an experience in Aguaytía Peru, in order to identify alliances that allow access to funds for natural resources management. The first methodology step was the mapping by saturation of stakeholders with their classification and prioritization for field work. The second step was to identify relationships through the link matrix. This process included secondary sources review and fieldwork where interviews, observation and attendance to key events were performed. With this information, the organizations network was constructed having stakeholders as nodes and relationships as links. Gephi software was used as support to facilitate the governance evaluation indicators construction process. As a research result, the most relevant forest governance stakeholders in Aguaytía were identified. Likewise, the network methodology evidenced that although formal power rests on public organizations, civil society organizations that work more closely with the population, exert real power.